Color enhancement mechanisms analysis of freeze-dried carrots treated by ultrasound-assisted osmosis (ascorbic acid-CaCl2) dehydration. (1st July 2022) - Lyu, Ying; Bi, Jinfeng; Chen, Qinqin; Wu, Xinye; Gou, Min; Yang, Xinrui
Graphical abstract: Highlights: UAA increased retention ratios of TCC (36.38%) and β -carotene (51.73%) of FDS. Samples treated by UAA had the highest raman intensity of CC in-plane expansion. Twelve color-related carotenoid products were identified by PCA-X analysis. 2- n -Pentylfuran was positively linearly correlated with the extractable color. β -Carotene dominated the surface color of FDS. Abstract: Color enhancement mechanisms of freeze-dried carrot sample (FDS) treated by ultrasound-assisted osmotic (ascorbic acid-CaCl2 ) dehydration (UAA) were comprehensively investigated from physical microstructures and color-related carotenoid compounds. Results of scanning electron microscope and confocal laser scanning microscopy showed that cells in samples treated by UAA were intact, had less porosity and showed stronger carotenoid autofluorescence. As for color-related compounds, UAA not only increased the retention ratios of total carotenoid content (36.38%) and β -carotene (51.73%) of FDS, but also preserved the high raman intensity of CC in-plane expansion (9986 A.U) and induced the formation of coloring-carotenoid-derivatives. Additionally, correlation and PCA-X model analysis showed that fresh carrot had higher extractable color value (78.46), which was positively linearly related to 2- n -pentylfuran ( p < 0.01), whereas FDS mainly affected the surface color that was dominated by β -carotene. This work provided the practical analysis and theoretical basis of color enhancement of freeze-dried carrot foods.